PENGEMBANGAN MULTIMEDIA GARDA "GARUDA DI DADA" PADA MATERI SIMBOL-SIMBOL PANCASILA KELAS I SDN SUDIMOROHARJO 2 TAHUN PELAJARAN 2024/2025 - Rohmawaty, Any; Fahmi Imron, Ilmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop interactive learning media based on the Canva application with the name Multimedia GARDA (Garuda di Dada) to increase the understanding of class I students at SDN Sudimoroharjo 2 on Pancasila symbols. The research method used is Research and Development (R&D) with the ADDIE model which consists of five stages: analysis, design, development, implementation and evaluation. The research results show that Multimedia GARDA has a validity level of 96% (media) and 94.2% (material), as well as a practicality level of 94% (teachers) and 97.3% (students). In addition, the effectiveness of this media is proven by a classical completion rate of 93% in extensive trials. Thus, the GARDA interactive multimedia based on the Canva application was declared valid, practical and effective for use as a medium in learning Pancasila and Citizenship Education. This media not only helps students understand the material more easily, but also increases students' active involvement in the learning process. Further development is recommended to expand the application of this multimedia to other materials at the elementary school level.